Longitudinal variability of size‐fractionated N2 fixation and DON release rates along 24.5°N in the subtropical North Atlantic. Issue 7 (15th July 2013) - Benavides, Mar; Bronk, Deborah A.; Agawin, Nona S. R.; Pérez‐Hernández, M. Dolores; Hernández‐Guerra, Alonso; Arístegui, Javier
Abstract : [1] Dinitrogen (N2 ) fixation and dissolved organic nitrogen (DON) release rates were measured on fractionated samples (>10 µm and <10 µm) along 24.5∘N in the subtropical North Atlantic. Net N2 fixation rates (N2 assimilation into biomass) ranged from 0.01 to 0.4 nmol N L −1 h −1, and DON release rates ranged from 0.001 to 0.09 nmol N L −1 h −1 . DON release represented ∼14% and ∼23% of >10 µm and <10 µm gross N2 fixation (assimilation into biomass plus DON release), respectively. This implies that by overlooking DON release, N2 fixation rates are underestimated. Net N2 fixation rates were higher in the east and decreased significantly toward the west ( rs  = −0.487, p  = 0.002, and rs  = −0.496, p  = 0.001, for the >10 µm and <10 µm fractions, respectively). The sum of both fractions correlated with aerosol optical depth at 550 nm (AOD 550 nm) ( rs  = 0.382, p  = 0.017) and phosphate (PO4 3− ) concentrations ( rs  = 0.453, p  = 0.018), suggesting an enhancement of diazotrophy as a response to aerosol inputs and phosphorus availability. In contrast, DON release was constant among size fractions and did not correlate with any of these variables. We also compared N2 fixation rates obtained using the 15 N2 dissolved and bubble methods. The first gave average rates 50% (49% ± 39) higher than the latter, which supports the finding that previously published N2 fixation rates are likely underestimated. We suggest that by combining N2 fixation and DON release measurements using dissolved 15 N2, global N2 fixation rates could increase enough to balance oceanic fixed nitrogen budget disequilibria. Key Points: DON release represents 20% of gross N2 fixation Bubble method N2 fixation rates are 50% lower than the dissolved method rates